ANALYSIS OF OPERATIONAL CHARACTERISTICS OF PURSE SEINE VESSELS BASED IN PPS NIZAM ZACHMAN USING VESSEL MONITORING SYSTEM DATA (Case Study at WPP 572) - Khansa Harisa Fakhrunnisa; Imam Triarso; Hendrik Anggi Setyawan (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2021)
A purse seine is one of the effective fishing gear, especially for catching pelagic fish. The fishing vessel based at Nizam Zachman Fishing Port Type A (PPSNZJ) and has an arrest permit in WPP 572 is dominated by purse seine. The surveillance function by the Ministry of Marine Affairs and Fisheries (KKP) is carried out by looking at the position data of the ship recorded by the VMS, as well as looking at the fishing logbook by fishermen. The study aimed to identify the characteristics of purse seine vessels using VMS data derived from KKP and looked at the degree of conformity of VMS data with fishing logbooks. The method used in this research is descriptive analysis methods. Fishing ground data is mapped using spatial data processing software. The results showed that the characteristics of purse seine vessels in 2017 were most in operation in April - July, 2018 in January - June, and in 2019 in May. Cross-matching fishing logbook with VMS data from 2017 - 2019 increased by 68% in 2017, 80% in 2018, and 83% in 2019.